2009
DOI: 10.1128/jvi.02593-08
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Functions of Herpes Simplex Virus Type 1 Regulatory Protein ICP0 That Are Critical for Lytic Infection and Derepression of Quiescent Viral Genomes

Abstract: Herpes simplex virus type 1 (HSV-1) is an important human pathogen that infects the majority of the population at an early age and then establishes a life-long latent infection in sensory neurones. Periodic reactivation of latent virus causes episodes of active disease characterized by epithelial lesions at the site of the original primary infection. As with all herpesviruses, the ability of HSV-1 to establish and reactivate from latency is key to its clinical importance and evolutionary success. Therefore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
153
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(169 citation statements)
references
References 88 publications
16
153
0
Order By: Relevance
“…and resulting in a productive EHV-1 infection in these cells. These results were consistent with recent work demonstrating the importance of protein acetylation and control of IE gene expression via HDACs during herpesvirus infections (Meier, 2001;Everett et al, 2009). In addition, we found that a higher number of CD172a + cells (12-14 %) were susceptible to EHV-1 infection following treatment with HDAC inhibitors compared with untreated cells (4 %).…”
Section: Ehv-1 Replication Is Delayed In Cd172asupporting
confidence: 82%
“…and resulting in a productive EHV-1 infection in these cells. These results were consistent with recent work demonstrating the importance of protein acetylation and control of IE gene expression via HDACs during herpesvirus infections (Meier, 2001;Everett et al, 2009). In addition, we found that a higher number of CD172a + cells (12-14 %) were susceptible to EHV-1 infection following treatment with HDAC inhibitors compared with untreated cells (4 %).…”
Section: Ehv-1 Replication Is Delayed In Cd172asupporting
confidence: 82%
“…pYD-C618 was derived from pYD-C245 and carried the N-terminally 1ϫFLAG-tagged M92 coding sequence that was expressed together with DsRed as a bicistronic transcript. pYD-C755 (a gift from Roger Everett, University of Glasgow Center for Viral Research), pYD-C678, and pYD-C780 were pLKO.1-based lentiviral expression vectors that carried a puromycin resistance marker (23,24). Both pYD-C780 and pYD-C678 were derived from pYD-C755, and they carried the C-terminally 3ϫFLAG-tagged M92 and UL92 coding sequences, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Production of lentiviral particles was achieved by transfection of 293T cells as previously described. 67 Following transduction with the pSLIK-A3A lentivirus, cells were selected in 1 mg/mL neomycin. After selection, cells were maintained in 0.5 mg/mL neomycin.…”
Section: Cell Linesmentioning
confidence: 99%
“…HepaRG cells were a gift from R. Everett (University of Glasgow) and were grown as previously described. 67 Inducible HepaRG-A3A and U2OS-A3A cells were constructed using a dual vector system with pLKO-EGFP-TetR and pLKO-TetO-A3A as previously described. 37,67 To construct inducible AT22IJE-A3A cell lines, HA-tagged A3A cDNA was inserted into an entry vector with the CMV promoter and upstream Tetracycline Response Element (pEN_Tmcs).…”
Section: Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation